Youth sport values: A comparative analysis between urban and rural students - Pujianto, Ferdy Alamsyah Eka; Ma’mun, Amung; Nugraha, Reshandi; Syarifatunnisa, Syarifatunnisa; Anira, Anira (Universitas Negeri Yogyakarta, 2025)
Sports and physical education have an essential role in improving morality in adolescents by implementing sports values, especially in overcoming juvenile delinquency and negative behaviour, one of which is bullying. This research seeks to investigate the comparison of sports values in students based on their environment. This study employs a numerical descriptive approach with a comparative survey design conducted in two schools, namely junior high schools and vocational high schools in Bandung Greater, with a total of 1,531 (869 students living in villages and 662 students living in cities) aged 14-17 years. The instrument in this study used the Youth Sport Values Questionnaire-2 (YSVQ-2), with data analysis using the Mann - Whitney U test. The Findings revealed a notable distinction in the Means Ranks value between villages and cities on Youth Sport Values (sig 0.011). The result show that urban areas have higher Youth Sport Values than rural areas. Several factors, including adequate sports facilities and a developing sports culture in the city, can influence this difference. These findings may indicate the importance of increasing access to sports facilities and emphasizing physical education in order to improve moral values and sportsmanship in students. Further research can examine more deeply the dynamics of the formation of sports values in various contexts using different research methods.